Islamische Theologie der Religionen. Eine Einführung und Bewertung - Mirsadri, Saida (Evangelische Theologie, 2024)
This article analyses the development of Islamic theology of religions in recent decades and classifies the various approaches into two main categories: exclusivism and pluralism. Furthermore, it argues that, in contrast to the historical Islamic tradition, which predominantly pursued a rather exclusivist approach, a theology of religions based exclusively on the Qurʾan offers significantly greater potential for an Islamic theology of pluralism.